Emergent magnetism and sublattice interplay in 3d-4f-5d double and quadruple perovskites - Attah-Baah, John Matthias (2025)
This thesis presents a systematic investigation of complex magnetic interactions in rare-earth containing perovskites, combining advanced neutron diffraction, magnetometry, and first-principles calculations to unravel the interplay between 3d-4f-5d exchange pathways, structural distortions, and functional properties. Through careful analysis of the double perovskite Nd2NiMnO6, we establish a monoclinic P21/n structure with almost complete B-site ordering of Ni/Mn and reveal a rich magnetic phase diagram featuring: (i) ferromagnetic ordering of Ni2+-Mn4+ sublattices at TN = 198 K exhibiting mean-field critical behavior, (ii) a re-entrant spin-glass state below TN , and (iii) non-collinear Nd3+ ordering below TN1 = 22 K driven by competing f − d and f − f exchange. The system demonstrates promising magnetocaloric performance (∆SM = 2.25 Jkg−1K−1 at 7 T) and significant spin-phonon coupling. The introduction of 5d Ir dopants in Nd2NiMn0.25Ir0.75O6 leads to three fundamental advances: (1) resolution of a unified Γ + 1 magnetic structure eliminating previous phase coexistence models, (2) precise determination of reduced Mn/Ir moments (0.38 µB) revealing strong spin-orbit frustration, and (3) discovery of coherent Nd3+ ordering with b-axis ferromagnetism and ac-plane canting. Remarkably, Ir mediates enhanced 3d-4f coupling despite suppressing B-site magnetization, demonstrating a novel route to engineer 3d-5d-4f interactions. Meanwhile, in NdSmNiMnO6, we identify a ferrimagnetic ground state (∆EFM-FiM ≈ 0.02 eV) stabilized by P21/n distortions (⟨Ni-O-Mn⟩ ≈ 146◦ ), with pronounced magnetostriction effects and spin-phonon coupling evidenced by Raman mode hardening. The material shows excellent magnetocaloric properties (RCP = 182 J/kg) and critical exponents revealing a mean-field to 3D Heisenberg crossover. First-principles calculations confirm the crucial role of orbital ordering and SOC-induced Sm3+ moment quenching. Finally, in the quadruple perovskite Er2CuMnMn4O12, we uncover four distinct magnetic transitions featuring spin reorientations between ±b and ±c axes, culminating in a low-temperature phase (TN4 = 7 K) with k = (0,0, 1 2 ) modulated Er1-Mn3 coupling. The sequence of transitions highlights the complex interplay between transition metal and rare-earth sublattices in these frustrated systems. Collectively, this work establishes design principles for manipulating competing exchange interactions in multifunctional perovskites, while demonstrating their potential for magnetic refrigeration and spintronic applications. The combination of structural tuning, 5d-orbital tuning, and sublattice-specific control presented here provides a roadmap for developing next-generation multifunctional materials with tailored magnetostructural properties.